Measuring the Effectiveness of AIOU Television for Students’ Learning - Syed Abdul Siraj (PJE, 2023)
Television makes education different from other teaching modes such as book, lecture, radio, computer, etc. television can make better learning in circumstances where regular teacher and educational institutions are not available. The use of television for distance education is f high currency especially in poor countries, where resources are limited, and population is unmanageable. This study evaluates AIOU television programs for students learning. The study finds that AIOU TV airtime, day and duration are not suitable to students. Although students mostly rely on the textbook assignments and examination, nevertheless TV programs make up deficiency for the missed tutorials and benefit students to some extent in writing assignments.